Identifikasi Gangguan Reproduksi Pada Pelaksanaan Inseminasi Buatan Sapi Donggala - Danus Danus; Mirajuddin Mirajuddin; Yohan Rusiyantono (Universitas Tadulako, 2020)
Research problem was lack of information regarding reproductive disorders that cause failure of artificial insemination and factors causing level and stages of reproductive failure of Donggala cattle. Therefore, the objective current study is to explore information of reproduction insemination failure on the stage of ovary and estrus abnormalities that influence the success of artificial insemination and factors causing reproductive disorders in Donggala cattle at each stage of reproduction. This research was a descriptive study carried out in Sindue sub-district, Labuan sub-district, Central Banawa sub-district and South Banawa in Donggala Regency which lasted from July to November 2016. The study used 121 samples of Donggala cattle belonging to the local farmers group. The cattle samples were cows that in dry period, not pregnant, not lactating and not in an estrus state. The variables of this study are reproductive disorders including anatomical ovarian abnormalities (ovarian hypoplasia, persistent corpus luteum) with rectal palpation approach (direct palpation) and abnormalities of estrus (subestrus, disguised estrus, anestrus) with observation. Fertility variables were non rutern rate (NRR) and conception rate (CR) as the focus on the success of Artificial Insemination (AI). Research variables showed that the percentage of reproductive disorders was much lower with NRR and CR values ​​than normal ovarian values ​​higher than AI evaluation results. The conception rate of the first AI results in Donggala cattle with normal anatomy and ovarian function was 95.6% (87/91 head). Furthermore, ovarian hypoplasia was 9%, (2/22 head), whereas persistent corpus luteum did not occur conception.